2016
DOI: 10.1186/s12888-016-0995-2
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety and suicidal ideation among 1st and 2nd generation migrants - results from the Gutenberg health study

Abstract: BackgroundEven though migrants constitute a large proportion of the German population, there is a lack of representative studies on their mental health. Hence, the present study explored mental health characteristics and suicidal ideation comparing 1st and 2nd generation migrants to non-migrants and subgroups within 1st generation migrants.MethodsWe investigated cross-sectional data of 14,943 participants of the Gutenberg Health Study (GHS), a population-based, prospective, single-center cohort study in Mid-Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 31 publications
5
64
2
2
Order By: Relevance
“…By comparison with a recent study of the German native population and a meta-analysis of European studies, 12-month prevalence rates of diagnosed depression were at 6% for the German population and 6.9% for the population of the European Union [52, 53]. Higher prevalence of depression among Turkish migrants of both migration generations compared to the host population and other migrant groups has been found in previous population-based studies [2631]. This paper demonstrates that individuals of older age and individuals with low socioeconomic status in particular display high prevalence rates of depressive disorders.…”
Section: Discussionmentioning
confidence: 64%
“…By comparison with a recent study of the German native population and a meta-analysis of European studies, 12-month prevalence rates of diagnosed depression were at 6% for the German population and 6.9% for the population of the European Union [52, 53]. Higher prevalence of depression among Turkish migrants of both migration generations compared to the host population and other migrant groups has been found in previous population-based studies [2631]. This paper demonstrates that individuals of older age and individuals with low socioeconomic status in particular display high prevalence rates of depressive disorders.…”
Section: Discussionmentioning
confidence: 64%
“…A more detailed discussion of this result can be found in Beutel et al. (). This finding is in line with previous studies with Turkish migrants in Germany (Igel, Brähler, & Grande, ; Morawa & Erim, ), however contradictory findings were reported by Mewes et al.…”
Section: Discussionmentioning
confidence: 80%
“…Further, Morawa and Erim () reported higher levels of depression and lower quality of life in Turkish migrants ( N = 109) compared to Polish migrants, who did not differ from the German population. As we have previously reported in another study based on the Gutenberg Health Study (GHS) data, about 24% of the participants reported a migration background (Beutel et al., ). Only first‐generation migrants (compared to second‐generation migrants) especially with Turkish origin reported increased depression and anxiety.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations